(MIS)ALIGNMENT BETWEEN THE STUDENTS’ ENGLISH COMPETENCY AND INDUSTRY DEMANDS: A CASE STUDY OF A VOCATIONAL HIGH SCHOOL IN MAKASSAR - Hanin, Ummi; Muliati, A.; Muhalim, Muhalim (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study examines the mismatch between the English competence of SMK SMTI Makassar students and industry demands. Using a mixed-methods approach, the study involved 12th-grade PM 3 students and an experienced English teacher through interviews, questionnaires, and document analysis. The results revealed a significant gap, with the main challenges including a lack of learning motivation, limited speaking and listening skills, and weaknesses in applying English in professional environments. The current curriculum does not fully meet industry needs due to the lack of focus on English for Specific Purposes (ESP). The study recommends integrating ESP into the curriculum, enhancing teacher professional development, and increasing student engagement in activities that develop speaking and listening skills. For future research, it is suggested to explore the implementation of ESP in vocational education and the use of contextual learning methods to improve students' readiness to enter the workforce.